2022
DOI: 10.1038/s41598-022-16860-6
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling structural and functional responses of native versus alien communities by canonical ordination analyses and variation partitioning with multiple matrices

Abstract: Freshwaters are under accelerated human pressure, and mollusk communities are among its most sensitive, threatened, and valuable components. To the best of our knowledge, the overall effects of damming, environment, space, time, and invasive alien mollusk species, on structural and functional responses of native mollusk communities were not yet compared. Using historical information and recent data from a river, we aimed to investigate and disentangle these effects and evaluate the differences in structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The findings demonstrated that environmental factors such as elevation, soil pH, temperature, and canopy cover were significant factors which constituted vegetation composition. Likewise, it also has been reported that these are key factors that significantly influence vegetation growth and distribution ( Ali et al, 2022 , Ali and Khan, 2022 , Sîrbu et al, 2022 , Chen et al, 2023 ). According to the CCA–ordination biplot, vegetation and topographic variables on axis 1 showed a significant correlation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The findings demonstrated that environmental factors such as elevation, soil pH, temperature, and canopy cover were significant factors which constituted vegetation composition. Likewise, it also has been reported that these are key factors that significantly influence vegetation growth and distribution ( Ali et al, 2022 , Ali and Khan, 2022 , Sîrbu et al, 2022 , Chen et al, 2023 ). According to the CCA–ordination biplot, vegetation and topographic variables on axis 1 showed a significant correlation.…”
Section: Discussionmentioning
confidence: 91%
“…For quantifying the relationship between vegetation abundance, environmental variables, and edaphic factors, principal component analysis (PCA), redundancy analysis (RDA), and Canonical correspondence analysis (CCA) has been widely used ( Ali et al, 2022 , Ali and Khan, 2022 , Sîrbu et al, 2022 ). In order to determine the most influential variables, we performed CCA-ordination, which explained 68.5 % of the variance in the data.…”
Section: Discussionmentioning
confidence: 99%
“…CWM‐sp). These methods include extensions of constrained ordinations, with predictors used for both the sites (environment) and for species (traits) as for example the popular fourth‐corner method and modifications of it (Dray et al, 2014; Dray & Legendre, 2008; Legendre et al, 1997; Sîrbu et al, 2022; ter Braak, 2012; Zelený, 2018), or the double‐constrained CCA (ter Braak, Šmilauer, et al, 2018). The fourth‐corner method, for example have been shown to provide the test with strongest power in the case of single linear trait effects on species distribution (Peres‐Neto et al, 2017; see also Section 4).…”
Section: Correcting Species‐ and Communniy‐level Analyses?mentioning
confidence: 99%